Meningkatkan Jiwa Wirausaha Melalui Pengembangan Pembelajaran Berbasis Produk Pada Siswa SMK - Sihwadi Sihwadi; Budi Santoso; Tri Kuat; Fitri Nur Mahmudah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research and development aim to evaluate the learning of creative products and entrepreneurship at Muhammadiyah 1 Vocational High School in Surakarta, develop product-based learning, and assess its suitability in fostering entrepreneurial spirit. The development method used is ADDIE, with 30 students from Class XII A as the experimental group, and 25 students from Class XII B as the control group. The research design adopts a quasi-experimental design known as the non-equivalent control group design. Data were collected through validation, observation, and questionnaires. The study results indicate that the current learning approach in this school is teacher-centered. However, the implementation of product-based learning using the ADDIE model effectively enhances students' entrepreneurial spirit. The T-test shows a significant difference in average scores between the experimental group (27.22) and the control group (2.944). Additionally, the N-Gain test indicates higher effectiveness (64.7450) for product-based learning compared to traditional methods (7.0428). Overall, this research proposes a highly suitable model for the development of product-based learning at Muhammadiyah 1 Vocational High School in Surakarta, with an emphasis on fostering entrepreneurial spirit